Exploring resistance to Pseudomonas aeruginosa infection in Caenorhabditis elegans - DiBernardo, Mercedes (My University, 2021)
Commensal microorganisms that colonize host surfaces can modulate susceptibility to infection. This can occur through direct inhibition of pathogen growth via competitive exclusion, or by modulation of the host environment to prevent pathogen dissemination and infection-mediated damage. However, understanding the mechanisms underlying these interactions is challenging due to the complexity of the human microbiome. The model organism Caenorhabditis elegans allows for the study of individual host-microbiota interactions, given they are bacterivorous and can be maintained monoxenically on a bacterial strain of interest. Here, we investigate the influence of human respiratory tract microbiota isolates on C. elegans susceptibility to Pseudomonas aeruginosa infection. Identifying isolates that differentially regulate resistance to infection will provide insight into how particular strains isolated from the human microbiome may act synergistically with P. aeruginosa or improve infection outcomes. A screen of isolates derived from the human respiratory tract was carried out using a liquid-based P. aeruginosa infection assay. Animals were first exposed to individual microbiotal isolates during development, prior to infection with a pathogenic strain of P. aeruginosa, PA14. This screen identified two non-pathogenic isolates of P. aeruginosa that increased survival during PA14 liquid killing, compared to animals pre-exposed to E. coli OP50. This protective phenotype was also induced by other mildly pathogenic strains of P. aeruginosa, including a laboratory strain with genetically attenuated virulence, PAO1 ∆vfr, as well as the pathogen Salmonella enterica. This work details the bacterial factors and host pathways that may regulate S. enterica and P. aeruginosa-mediated protection from PA14 liquid killing.